KEMAMPUAN ADAPTASI MASYARAKAT TRANSMIGRAN JAWA DI LAHAN GAMBUT DESA JEJANGKIT TIMUR KECAMATAN JEJANGKIT KABUPATEN BARITO KUALA - Syarifuddin Syarifuddin; Deasy Arisanty; Herry Porda Nugroho Putro; M. Zainal Arifin Anis (EnviroScienteae, 2019)
The research aims to examine the adaptation ability of the Transmigrant community in terms of the natural/physical environment and the ability of the transmigrant community in terms of social culture. This research uses quantitative research methods. Data collection techniques using interviews, observations and documentation. Data analysis uses qualitative data, data reduction, data presentation, and data verification. The results showed that the Transmigrant Society of Java strives to adapt to the new environment and try to find other businesses such as building work, truck drivers, officers, and others with side business expectations. It can help to increase family economic income, in the process of community peatland tends to garden palm, rubber, and oranges and some are farmed. Adaptation in terms of the cultural environment, the Javanese transmigration Society has no difficulty proved by the cooperation of community in marriage, religious and other cultures.